Сибирская амазонка: роман / Ирина Мельникова - Мельникова Ирина Александровна (Незнакомка, 2011)
Экземпляры: ф. 4 (20120514) / Инвентарный номер: 98550 / Цена: 75 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 48 / ББК: 84(2Рос=Рус)6